Breastfeeding during Pregnancy: Position Paper of the Italian Society of Perinatal Medicine and the Task Force on Breastfeeding, Ministry of Health, Italy. (February 2014) - Cetin, Irene; Assandro, Paola; Massari, Maddalena; Sagone, Antonella; Gennaretti, Raffaella; Donzelli, Gianpaolo; Knowles, Alessandra; Monasta, Lorenzo; Davanzo, Riccardo; ,
As more women breastfeed for longer, it is increasingly likely that women may be still breastfeeding when they become pregnant again. The Italian Society of Perinatal Medicine (SIMP) Working Group on Breastfeeding has reviewed the literature to determine the medical compatibility of pregnancy and breastfeeding. We found no evidence indicating that healthy women are at higher risk of miscarriage or preterm delivery if they breastfeed while pregnant. No evidence indicates that the pregnancy–breastfeeding overlap might cause intrauterine growth restriction, particularly in women from developed countries. Little information is available on the composition of human milk of pregnant women, and we found no data on the growth of infants nursed by a pregnant woman. However, both the composition of postpartum breast milk and the growth of the subsequent newborn appear to be partly affected, at least in developing countries. SIMP supports breastfeeding during pregnancy in the first 2 trimesters, and we believe it to be sustainable in the third trimester. Based on the hypothetical risk, caution may be warranted for women at risk of premature delivery, although no evidence exists that breastfeeding could trigger labor inducing uterine contractions. In conclusion, currently available data do not support routine discouragement of breastfeeding during pregnancy. Further studies are certainly needed to explore the consequences of breastfeeding during pregnancy on maternal health, on the breastfed infant, on the embryo/fetus, and, subsequently, on the growth of the newborn.